Pharmacist-driven optimization of presumptive psittacosis management: a case report of rapid clinical resolution - Ji, Guowen; Duan, Jingjing (The Journal of Infection in Developing Countries, 2026)
Introduction: Chlamydia psittaci has a high incidence of pneumonia after infection, but clinical diagnosis still faces challenges due to the lack of specific clinical manifestations and low positive rates in routine testing. Case presentation: A 60-year-old female patient with community-acquired pneumonia (CAP) failed to respond to initial intravenous antimicrobial therapy with cefmetazole/ciprofloxacin followed by piperacillin-tazobactam/levofloxacin, exhibiting persistent fever and worsening symptoms. Serial laboratory testing revealed progressive elevation of inflammatory markers, with C-reactive protein (CRP) rising from 110.2 to 120.9 mg/L and procalcitonin (PCT) from 1.37 to 2.15 ng/mL. Essential bronchoscopic examination and metagenomic next-generation sequencing (mNGS) could not be performed due to patient refusal, creating a diagnostic deadlock. The clinical pharmacist identified avian exposure during medication rounds, enabling presumptive diagnosis of psittacosis. Immediate pharmacist-initiated interventions included discontinuation of levofloxacin and commencement of targeted oral minocycline therapy. Clinical resolution occurred within 48 hours with defervescence and symptomatic improvement. Subsequent minocycline-induced nausea and diarrhea were effectively managed through pharmacist-instructed co-administration with food. Continuous clinical improvement facilitated discharge on oral minocycline, with follow-up imaging confirming complete resolution of pulmonary infiltrates. Conclusions: This case underscores the value of pharmacist-led pharmaceutical assessment in uncovering atypical infection etiologies and guiding targeted antimicrobial therapy.